2009
DOI: 10.1007/s12648-009-0045-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation of radon concentrations in soil and groundwater and its correlation with radon exhalation rate from soil in Budhakedar, Garhwal Himalaya

Abstract: : Radon was measured in soil-gas and groundwater in the Budhakedar area of Tehri Garhwal, India in summer and winter to obtain the seasonal variation and its correlation with radon exhalation rate. The environmental surface gamma dose rate was also measured in the same area. The radon exhalation rate in the soil sample collected from different geological unit of Budhakedar area was measured using plastic track detector (LR-115 type II) technique. The variation in the radon concentration in soil-gas was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…Similarly, the recorded radon concentrations were compared with the European Commission (EU 2001) recommended action level of 100 Bq/L for pubic water supplies; and it was apparent that radon concentration exceeded the action level in 20% of samples (viz., 13 groundwater samples). The mean and the range values of radon concentration recorded in the present study are on higher side compared to the result reported by Kumar et al (2017) Prasad et al (2009) as the latter reported radon concentration ranging from 8-3047 (average: 510 Bq/L) in the groundwater collected and analyzed from parts of Garhwal Himalayas, India. Figure 3 and it well fits to a typical log-normal distributions.…”
Section: Distribution Of Radon Concentrationcontrasting
confidence: 65%
“…Similarly, the recorded radon concentrations were compared with the European Commission (EU 2001) recommended action level of 100 Bq/L for pubic water supplies; and it was apparent that radon concentration exceeded the action level in 20% of samples (viz., 13 groundwater samples). The mean and the range values of radon concentration recorded in the present study are on higher side compared to the result reported by Kumar et al (2017) Prasad et al (2009) as the latter reported radon concentration ranging from 8-3047 (average: 510 Bq/L) in the groundwater collected and analyzed from parts of Garhwal Himalayas, India. Figure 3 and it well fits to a typical log-normal distributions.…”
Section: Distribution Of Radon Concentrationcontrasting
confidence: 65%